AUGMENTED REALITY VIRTUAL MIRRORS-THE INNOVATIVE DRIVERS FOR CONSUMER PURCHASE DECISION-MAKING - Rishab Manocha; Mridul Dharwal; Nitendra Kumar; Dhrubajyoti Bhowmik; Vinay Kumar Yadav (Proceedings on Engineering Sciences)
This paper emphasizes the importance of Augmented Reality (AR) and its impact on customer purchasing decisions through in-store Virtual Mirrors (VMs) built through real-time applications using digitalization processes. The paper contributes to the emerging topic of Consumer Purchase Decision-Making by examining international brands that use VM Technology to create immersive customer experiences and how it affects consumer decision-making. The study takes into consideration, as a case study, iconic American Brand Tommy Hilfiger, which has a multi-level store on the prestigious Regent Street in London opened in 2006. The study's data was gathered from reports made by 20 British nationals residing in London who utilized the publicly available VMs at the specified retailer. The process commenced with the editing and organization of responder reports, selected according to the level of saturation in several VM scenarios. The observations and conclusions yielded a lot of empirical data to analyze. This level identified 870 conceptual categories related to Virtual Mirrors using content and sentiment analysis. In the respondents' remarks, 1,279 instances pertinent to the study's topic were identified, along with the most utilized terms.